2007
DOI: 10.1016/j.jasms.2007.03.001
|View full text |Cite
|
Sign up to set email alerts
|

B-DNA Helix Stability in a Solvent-Free Environment

Abstract: B-DNA is the most common DNA helix conformation under physiological conditions. However, when the amount of water in a DNA solution is decreased, B-to-A helix transitions have been observed. To understand what type of helix conformations exist in a solvent-free environment, a series of poly d(CG) n and mixed sequence DNA duplexes from 18 to 30 bp were examined with circular dichroism (CD), ESI-MS, ion mobility, and molecular dynamics. From the CD spectra, it was observed that all sequences had B-form helices i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 45 publications
3
67
0
Order By: Relevance
“…This does not necessarily mean that the gas-phase conformations of 6-and 7-charge states are A-and B-helices, but helps to understand conclusions previously derived solely based on more densely charged duplexes. 17,18 When starting from the B-form, MD simulations always show spontaneous hydrogen bonds formation between phosphate groups situated on each side of the minor groove (supporting information Movie S1 and Figure S8). This causes the "zipping" of the minor groove.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This does not necessarily mean that the gas-phase conformations of 6-and 7-charge states are A-and B-helices, but helps to understand conclusions previously derived solely based on more densely charged duplexes. 17,18 When starting from the B-form, MD simulations always show spontaneous hydrogen bonds formation between phosphate groups situated on each side of the minor groove (supporting information Movie S1 and Figure S8). This causes the "zipping" of the minor groove.…”
Section: Resultsmentioning
confidence: 97%
“…16 The Bowers group later explored the gas-phase structure of DNA duplexes by IMS. 17,18 By comparing the experimental collision cross section (CCS) of d(GC) n duplexes with those obtained on duplexes relaxed by short (5-ns) MD, they showed that the gas-phase structures resemble an A-helix for the short duplexes (8)(9)(10)(11)(12)(13)(14)(15)(16)-mer) and a B-helix for longer ones (>18-mer). It is worth noting that Bowers' IMS experiments were performed in non-native solution conditions (49:49:2 mixture of H 2 O:MeOH:NH 4 OH) and on high charge states (1 negative charge per 2 base pairs), raising questions on whether this represents what happens in native conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This does not necessarily mean that the gas-phase conformations of 6– and 7– charge states are A- and B-helices, but it helps to understand conclusions previously derived solely based on more densely charged duplexes. 21,22 …”
Section: Resultsmentioning
confidence: 99%
“…Their experimental CCS is far smaller than the one that a B-helix would adopt, and also far smaller than the values reported by the Bowers group on more densely charged duplexes (Baker & Bowers, 2007;Gidden, Ferzoco, Baker, & Bowers, 2004). Multiple co-existing conformations are observed, in that the CCS distributions are much broader than the instrumental peak width.…”
mentioning
confidence: 62%